Quantifying Chemical Expansion of Non-Stoichiometric Oxide Thin Films: Challenges and Opportunities. (2nd June 2015) - Swallow, Jessica G.; Kim, Jae Jin; Chen, Di; Bishop, Sean R.; Smith, James F.; Tuller, Harry L.; Van Vliet, Krystyn J.
Abstract : Non-stoichiometric oxides within active components of solid oxide fuel cells (SOFCs) can exhibit chemical expansion, including measurable changes in lattice parameter or volume as a function of point defect concentrations. Robust SOFC design requires knowledge of how chemical expansion contributes to mechanical strains at interfaces that can promote dislocation mobility, delamination, or fracture. Direct measurement of chemical expansion via X-ray diffraction or dilatometry typically requires long time scales (minutes to hours) to allow equilibration of gas atmospheres or bulk samples, or to allow adequate signal detection in the absence of synchrotron access. Here, we discuss current methods of measuring chemical expansion in situ and consider how they may be extended to investigate the expansion of thin films or fuel cell stacks. A facile approach to measuring dynamic chemical expansion under in operando conditions of SOFC electrodes could facilitate improved design of materials that withstand large chemomechanical changes during SOFC operations.